Dynamic feedback control through wall suction in shear flows. Issue 1 (18th November 2019) - Linkmann, Moritz; Eckhardt, Bruno
Abstract: Flow control is of interest in many open and wall‐bounded shear flows in order to reduce drag or to avoid sudden large fluctuations that may lead to material failure. An established means of control is the application of suction through a porous wall. Here, we combine suction with a feedback strategy whereby the suction velocity is adjusted in response to either the kinetic energy or the shear stress at the bottom wall. The control procedure is then used in an attempt to stabilize invariant solutions and to carry out direct numerical simulations with a prescribed value of the friction coefficient.